“Now once again”, about the edition of the book-object Ἔρως/Eros políglota. Lenguas, traducción y sentido de un dios antiguo (El Hilo de la Fabula, 2022)
Throughout the history of Occidental thinking, love and its effect have been among the most explored subjects. The Ancient Greeks built a whole imaginary around the god Eros and how he affects people, but it was the current relevance of this imaginary that brought us to write the book Eros Políglota. Lenguas, traducción y sentido de un dios antiguo. The paper below addresses the methodology we applied to write the book, and is presented in two sections: first, we explore how the Greek language builds the erotic experience and describes the god Eros during the Archaic and Classic Greece, and how the building of that experience is still relevant nowadays. Secondly we focus on the «book-object» as the form we choose for our book, the reason why we decided to go that way and how the decision is related to the original passages we translated. We suggest that: i) The power of the Greek imaginary over Eros is built from the language in the expressions, grammar, metrics and rhetoric developed by the authors we translated; ii) The decision to use a book-object in the form of a capsa as a reading proposal responds to the interest of accommodating a multiplicity of meanings that are best suited in this format to our selection and translation project.
Keywords: Eros; Translation; greek archaic and classic literature; edition; book-object